Evaluation of Management of the Use of Information and Communication Technology - Heri Kuswara; Ihsan Mustofa (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
These stages in Terry's management function are known as Planning, Organizing, Actuating, and Controlling (POAC). To measure the success of the use of information and communication technology in the learning space, an evaluation of the management stages that are carried out is needed. Stufflebeam's Model or CIPP Model is an evaluation model that can be used to evaluate the extent to which an educational program can achieve its goals. Madrasah Aliyah (MA) Al-Musthofa is one of the madrasas that used information and communication technology in the learning room. The management stages become a reference for Madrasah aliyah Al-Musthofa in the use of information and communication technology in the learning room. This research with a descriptive qualitative approach provides an evaluation description that the management function has been carried out well by Madrasah Aliyah Al-Musthofa but there are still various shortcomings and weaknesses both in terms of human resources and other resources. These shortcomings and weaknesses have an impact on not achieving the objectives of the use of information and communication technology in the learning space at Madrasah aliyah al-Musthofa.